Identification of Novel Immune Cell-Relevant Therapeutic Targets and Validation of Roles of TK1 in BMSCs of Systemic Lupus Erythematosus - Chen, Fangru; Meng, Jian; Yan, Wenjie; Wang, Mengjiao; Jiang, Yunfei; Gao, Jintao (Frontiers in Molecular Biosciences, 2022)
Objective: Systemic lupus erythematosus (SLE) displays the characteristics of abnormal activity of the immune system, contributing to diverse clinical symptoms. Herein, this study was conducted for discovering novel immune cell-relevant therapeutic targets. Methods: The abundance of diverse immune cells was estimated in PBMCs of SLE and healthy controls from the GSE50772 dataset with CIBERSORT approach. Immune cell-relevant co-expression modules were screened with WGCNA and relevant characteristic genes were determined with LASSO algorithm. Inflammatory chemokines were measured in serum of twenty SLE patients and twenty controls through ELISA. Bone marrow mesenchymal stem cells (BMSCs) were isolated and TK1 expression was measured in BMSCs through RT-qPCR and western blotting. TK1-overexpressed and TK-1-silenced BMSCs of SLE were conducted and apoptosis and cell cycle were measured with flow cytometry. Apoptosis-, cell cycle- and senescence-relevant proteins were tested with western blotting. Results: We determined three co-expression modules strongly linked to immune cells. Five characteristic genes (CXCL1, CXCL2, CXCL8, CXCR1 and TK1) were screened and ROC curves proved the excellent diagnostic performance of this LASSO model. Inflammatory chemokines presented widespread up-regulations in serum of SLE patients, demonstrating the activation of inflammatory response. TK1 expression was remarkably elevated in SLE BMSCs than controls. TK1 overexpression enhanced IL-1β expression, apoptosis, cell cycle arrest, and senescent phenotypes of SLE BMSCs and the opposite results were proved in TK1-silenced SLE BMSCs. Conclusion: Collectively, our findings demonstrate that silencing TK1 alleviates inflammation, growth arrest and senescence in BMSCs of SLE, which highlights TK1 as a promising therapeutic target against SLE.